Knowledge and Perceptions of Latent Tuberculosis Infection among Chinese Immigrants in a Canadian Urban Centre. (24th November 2015) - Gao, Jie; Berry, Nicole S.; Taylor, Darlene; Venners, Scott A.; Cook, Victoria J.; Mayhew, Maureen
Abstract : Background . Since most tuberculosis (TB) cases in immigrants to British Columbia (BC), Canada, develop from latent TB infection (LTBI), treating immigrants for LTBI can contribute to the eradication of TB. However, adherence to LTBI treatment is a challenge that is influenced by knowledge and perceptions. This research explores Chinese immigrants' knowledge and perceptions towards LTBI in Greater Vancouver. Methods . This mixed methods study included a cross-sectional patient survey at BC's Provincial TB clinics and two focus group discussions (FGDs) with Chinese immigrants. Data from FGDs were coded and analyzed in Simplified Chinese. Codes, themes, and selected quotes were then translated into English. Results . The survey identified a mean basic knowledge score: 40.0% (95% CI: 38.3%, 41.7%). FGDs confirmed that Chinese immigrants' knowledge of LTBI was low, and they confused it with TB disease to the extent of experiencing LTBI associated stigma. Participants also expressed difficulties navigating the health system which impeded testing and treatment of LTBI. Online videos were the preferred format for receiving health information. Conclusion . We identified striking gaps in knowledge surrounding an LTBI diagnosis. Concerns of stigma may influence acceptance and adherence of LTBI treatment in Chinese immigrants. Integrating these findings into routine health care is recommended.